Depression, Anxiety, and Stress among Health Science Students Belonging to Non-affluent Families - Kartheek R. Balapala; Balakrishnan Subramanian (Issues and Development in Health Research Vol. 6, 2021)
Introduction: In due course of training, the health science students confront significant stress in psychological, academic, and existential domains. Coping strategies may be needed for a medical student placed in a new school with a new teaching schedule. Objective: To study depression, anxiety and stress (DAS) levels and their associated factors among the health science students belonging to academic years 1 to 5 of the University Tunku Abdul Rahman in Malaysia. Methods: Undergraduate Health Science students learning medicine, traditional Chinese medicine, and physiotherapy courses were selected for a questionnaire-based descriptive correlational study. DAS scale questionnaire 21 (DASS 21) was used for analyzing the levels of stress and other parameters, and General health questionnaire 12 (GHQ 12) was used for the assessment of general health among 134 students on a week before their periodical examinations. Results: Severe depression was found in 9.7% of students learning health science courses. About 42% of students showed combined effects of depression and anxiety. The three domains of DAS were significantly correlated. Depression was found significantly among female students (38%) more than male students (18%). DAS levels were significantly high among the first-year students as compared to the final year graduating students in the MBBS course. Depression and stress levels and their associations were found high among students those who were encountered adverse life events in the recent past 1 year before the study. GHQ scores for 134 participants of all health science courses were >6 in 39.55%, equal to 6 in 9.7%, and others in 50.75% of student participants. Conclusion: A significant number of students learning health sciences were having higher levels of DAS and were associated with several important factors. There is a need to adopt better counselling and mentoring techniques among university staff with better connectivity among health science students. Proactive steps must be implemented at the community level for the amelioration of the drawbacks.